Reconstruction of Islamic Family Law: Analyzing Marital Issues Through Multimedia - Okti Nur Hidayah; Muhammad Fuad Zain; Anis Ma’rifah (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
The development of social media and technological disruption has occurred increasingly massively, where the media has become the primary means of knowledge transformation. One example is the construction of a discourse on marriage that becomes public consumption through social media. This paper aims to explain the process of reforming Islamic family law through multimedia. This research uses a qualitative research method in which the researcher seeks to describe the media's role in reforming Islamic family law. The approach used in this research is digital ethnography. Reconstructing Islamic family law through multimedia can be a very effective tool to educate the public about Islamic family law, clarify misconceptions, and facilitate open discussions on family-related legal issues within the Muslim community. Educational videos, podcasts, webinars, infographics and educational graphics, e-learning platforms, documentaries, social media, mobile applications and online consultations are some of how multimedia can be used to reconstruct Islamic family law.